When Rain Falls - Stewart, Melissa (Atlanta, Georgia Peachtree, 2008)
Tells what different animals do when a thunderstorm hits.
elementary
Keywords: Stewart, Melissa -- Rain and rainfall - juvenile literature -- animal behavior - juvenile literature -- rain and rainfall -- animals - habitats and behavior